Environmental management of industrial waste water with mercury from gold mining worldwide: state of art - Garzón Gutiérrez, Jennyfer Magdalia; Rodríguez Miranda, Juan Pablo (Universidad y Salud, 2015)
Introduction: Given the social and environmental problems caused by artisanal and small-scale gold mining (MAAPE), the review of the state of art was conducted in this paper in terms of environmental management of wastewater with mercury (Hg) worldwide. Materials and methods: The review was conducted from scientific articles published over the past five years. It was found that interventions to address the impacts by Hg in the MAAPE have been focused on the creation of laws to reduce and eliminate the use of mercury, which have been ineffective. Results: In this way, 62% of the tested sites are in a category of nonexistent environmental management, 8% is in reactive phase and 31% in charge phase, while no process was found in proactive or competitive management. Moreover, several experimental studies on wastewater treatment with Hg were found, which could be adapted to the management of liquid waste from the MAAPE found.